Analysis Of The Fulfillment Of The Housing Backlog Low-Income Community (MBR) And The Amount Of Land Used In The City Of Palembang - Didy Aribowo; Heni Fitriani; Febrian Hadinata (Green Publisher Indonesia, 2024)
This study aims to analyze the amount of low-cost housing backlog (MBR) in the city of Palembang in 2025; calculate the number of uninhabitable houses as an addition to the housing backlog figure; calculate the land requirement for MBR housing in meeting the backlog in the city of Palembang; analyze the zoning for the placement of MBR housing with spatial patterns and spatial structures. This research uses a descriptive research method with a quantitative approach. The study was conducted in the city of Palembang, which is the seventh city with the highest housing backlog in Indonesia, with a backlog figure reaching 122,932 houses. Data collection was done through face-to-face interviews by asking questions to the chairman of the South Sumatra Real Estate Association, the Palembang City Perkim Department, about housing backlog in Palembang. Data analysis used the Cambridge method, Sustainable Development Goals method, Minister of Public Works and Public Housing Regulation No.995/KPTS/M/2021 method, & Regional Regulation No.05 of 2022 method. The latest backlog figure recorded in 2018 was 122,932 dwellings (Palembang City Perkim Department, 2021). Uninhabitable houses (RTLH) in Palembang in 2019 experienced a decrease and continued to increase in 2020. The effective land requirement for MBR housing and Fasum Fasos with a ratio of 60:40 is calculated, followed by data on built houses according to REI data in Palembang. The zoning for the placement of MBR housing land in Palembang, which reached 4,987.62 ha in 2025, must consider the spatial patterns and spatial structures of Palembang City.